1999
DOI: 10.1046/j.1365-3040.1999.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vp1 and water channel proteins during seed germination

Abstract: Germination of seeds from individual seed capsules ofMesembryanthemum crystallinum (common ice plant) is spread out over time with some seeds germinating within 1 d (early, E) and others germinating up to more than 4 weeks after imbibition (late, L). L-seeds are characterized by a lack of expression of Cdc2-related transcripts and an increase of Vp1-transcripts after water uptake, while Cdc2-related transcripts increase early and Vp1 decline early in E-seeds. Maintenance of Vp1 transcription, which can be disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…This is different from observations in A. thaliana, corn and rice, where Vp1 transcripts are associated with seed maturation and are low or not detectable in germinating seeds (Giraudat et al, 1992, Hattori et al, 1994, McCarty et al, 1991, Parcy et al, 1994. In contrast to the dormant seeds, Mvp1 transcripts disappear from early-germinating seeds within a few days following imbibition but persists longer in late-germinating seeds (Fukuhara et al, 1999). Here, we characterize the ice plant Mvp1 transcript.…”
Section: Introductioncontrasting
confidence: 62%
See 4 more Smart Citations
“…This is different from observations in A. thaliana, corn and rice, where Vp1 transcripts are associated with seed maturation and are low or not detectable in germinating seeds (Giraudat et al, 1992, Hattori et al, 1994, McCarty et al, 1991, Parcy et al, 1994. In contrast to the dormant seeds, Mvp1 transcripts disappear from early-germinating seeds within a few days following imbibition but persists longer in late-germinating seeds (Fukuhara et al, 1999). Here, we characterize the ice plant Mvp1 transcript.…”
Section: Introductioncontrasting
confidence: 62%
“…uptake, such as those encoding cdc2 and water channel proteins, and studied their expression. While late-germinating seeds took up water and expressed transcripts for water channel proteins, transcripts indicative of cell cycle progression and cell division were expressed much later than in early-germinating seeds (Fukuhara et al, 1999) (and data not shown).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations